Pete the Cat saves Christmas - Litwin, Eric; Dean, James, 1957-; Moore, Clement Clarke, 1779-1863. (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2019)
"Spend the holidays with your favorite blue cat! In this rockin' spin on the traditional tale The Night Before Christmas, Pete the Cat proves that giving your all in the spirit of Christmas is the totally groovy thing to do."--Publisher's description
Publication date taken from publisher's Web site
Ages 4-8
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Santa Claus -- (Fictitious character) -- Juvenile fiction; Santa Claus -- Easy picture; Cats -- Juvenile fiction; Stories in rhyme; Cats -- Easy picture; Christmas -- Easy picture; Holidays -- Easy picture; Stories in rhyme; Cats -- Fiction; Christmas -- Fiction; Santa Claus -- Fiction; Christmas stories; Adaptations; picture books; Christmas stories; Stories in rhyme; Christmas fiction; Animal fiction; Picture books; Adaptations